OPTIMALISASI PENGELOLAAN SUMBER DAYA AIR DI KABUPATEN MUARA ENIM UNTUK MENDUKUNG PENYEDIAAN AIR BERSIH YANG EFISIEN - Oktavianus Chayadi; Edison Hatoguan Manurung (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study analyzes the availability of clean water in Muara Enim Regency by focusing on the balance between water resource potential and community water demand up to the year 2035. The analysis employs a water balance method using a descriptive qualitative and quantitative approach, based on the processing and evaluation of secondary data from multiple sources, including population data, climatological data, and information on the existing water supply system. The data were obtained from the Central Bureau of Statistics (BPS), the Meteorology, Climatology, and Geophysics Agency (BMKG), as well as the Water Supply System Master Plan (RISPAM) of Muara Enim Regency as a technical reference. The results of the analysis indicate that the Enim River has an average discharge of approximately 56 m³/s, equivalent to 4.8 billion liters per day, while domestic water demand in 2025 is estimated at 11.86 million liters per day and is projected to increase to 13.79 million liters per day by 2035. The water balance analysis conducted in this study reveals a surplus of approximately 4.82 billion liters per day, indicating that water availability is quantitatively sufficient. Nevertheless, the analysis also shows that the capacity of water treatment and distribution systems remains suboptimal, as reflected by limited treatment capacity and relatively high water losses. Based on the calculations and evaluations carried out in this study, it is recommended to increase water treatment capacity, develop balancing storage facilities, and rehabilitate the distribution network in order to reduce water losses and improve clean water service coverage by 2035.